(untitled) (Materiali di Estetica. Terza serie, 2016)
The essay draws on the content and the title of a Neri’s work published in 1982, as well as on the unpublished work of 2001, focused on a new thinking about phenomenology. The aim of the article is to propose an overall interpretation, both critic and expositive of these works in order to show their possibility of a future sequence in another “after”: Europe, the horizon of a cosmopolitan world, precisely, “after” the disappearance of countries of “implemented socialism” (as Urss bloch and the Republic of the East were called). Neri declared the need of a return to epoché that is a renewed “wonder”, although the mundane naturalism and the technical triumph: that is a suggestion valid today even more, in a world that is globalized and distressed by the migrants drama.